2021
DOI: 10.21891/jeseh.771331
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of STEM Education on the 7th Grade Students’ Critical Thinking Skills and STEM Perceptions

Abstract: Critical thinking and STEM career perception are important in 21 th century and STEM education is necessary to promote middle school students' critical thinking skills and STEM perception. In this research we aim to research the effects of engineering design-based STEM education on the middle school students' critical thinking skills and STEM perceptions. In this case study, STEM activities were developed according the subjects of "Reflections in Mirror" and "Absorption of Light" and prepared activity booklet.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 43 publications
(45 reference statements)
1
19
0
1
Order By: Relevance
“…In addition, the STEM content in the electronic teaching material also influences the results obtained. This is in line with previous research which has proven that STEM is relevant to apply in developing students' critical thinking skills (Hacioğlu & Gülhan, 2021;Mater et al, 2020). These results are also related to the fact that the process of generating problem solutions in a STEM context affects the development of students' critical thinking skills (Mater et al, 2020;Rizaldi et al, 2020;Savran Gencer & Dogan, 2020;Sumarni & Kadarwati, 2020).…”
Section: Effectiveness Of Petms On Critical Thinkingsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, the STEM content in the electronic teaching material also influences the results obtained. This is in line with previous research which has proven that STEM is relevant to apply in developing students' critical thinking skills (Hacioğlu & Gülhan, 2021;Mater et al, 2020). These results are also related to the fact that the process of generating problem solutions in a STEM context affects the development of students' critical thinking skills (Mater et al, 2020;Rizaldi et al, 2020;Savran Gencer & Dogan, 2020;Sumarni & Kadarwati, 2020).…”
Section: Effectiveness Of Petms On Critical Thinkingsupporting
confidence: 91%
“…These results are also related to the fact that the process of generating problem solutions in a STEM context affects the development of students' critical thinking skills (Mater et al, 2020;Rizaldi et al, 2020;Savran Gencer & Dogan, 2020;Sumarni & Kadarwati, 2020). STEM accommodates student activities to be more active in groups to solve a problem by evaluating all the ideas obtained and making decisions to solve the problem (Hacioğlu & Gülhan, 2021). In other words, PETMS assists students to build their own knowledge by encouraging them to be active in learning, identifying possible solutions, selecting data or information, giving opinions about the selected data and finally being able to provide possible problem-solving.…”
Section: Effectiveness Of Petms On Critical Thinkingmentioning
confidence: 99%
“…A review of the literature revealed that STEM evolved out of government policy, especially from within the National Science Foundation (NSF) (Marrero et al, 2014). NSF first used the acronym SMET for science, mathematics, engineering, and technology in the early 1990s, but determined that this acronym sounded too much like "smut", and then STEM was born in 2001 (Hacioglu & Gulhan, 2021;Marrero et al, 2014;Sanders, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…STEM education delivers learning benefits to students since students can explore their creativity to solve a problem through some disciplines (Suratno et al, 2020). When students apply STEM in context, it makes connections between school, community, work, and the global enterprise with the ability to compete in the new economy (Bruce-Davis et al, 2014;Hacioglu & Gulhan, 2021). STEM education aims to equip students Preprint version of: Jamali, Seyedh Mhboobeh., Ale Ebrahim, Nader.…”
Section: The Importance Of Stem Educationmentioning
confidence: 99%
“…STEM education focuses on three themes: acquiring problem solving skills, being innovative and able to design because STEM in education aims to bring individuals at an interdisciplinary level covering the fields of Science, Mathematics, Engineering and Technology (Korkmaz et al, 2020). STEM education is also evaluated as a bridge between education and career for students (Hacioglu & Gulhan, 2021).…”
Section: Introductionmentioning
confidence: 99%